WASTE MANAGEMENT IN SAUMLAKI CITY, TANIMBAR ISLANDS REGENCY - Hijriyani, Dewi; Ponto, Iriane Sosiawaty; Madjid, La (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
This research focuses on the practices of waste collection and disposal. Utilizing a qualitative methodology approach, the study employs interviews, observations, documentation, and literature reviews as data collection techniques in a